THU0442 High Incidence of Hip Fracture and Non-Vertebral Osteoporotic Fracture in Low Income Community-Dwelling Elderly: A Population-Based Prospective Cohort Study in Brazil. the SÃO Paulo Ageing & Health (SPAH) Study. (10th June 2014) - Domiciano, D.S.; Machado, L.G.; Lopes, J.; Figueiredo, C.; Menezes, P.; Caparbo, V.; Takayama, L.; Pereira, R.M.R.
Abstract : Background: There is considerable variability in the incidence of hip fracture among countries, even among different geographical areas within the same country. In Brazil, population differences in occurrence of hip fracture are probably related to the huge size of the country, the substantial ethnical miscegenation and distinct lifestyle habits within the Brazilian territory. Longitudinal studies on incidence of hip fracture in the Brazilian population are scarce and the results are hampererd by incomplete capture of cases and short follow-up time. Moreover, there is no prospective study on incidence of non-vertebral fractures beyond the hip. Objectives: To describe the incidence of hip and non-vertebral fracture in elderly community from a prospective population-based study. Methods: Incidence of hip and non-vertebral fracture were determined in 707 women and men from community, aged 65 years or older. Specific questionnaire (clinical and anthropometric data), including personal history of fragility fracture in non-vertebral osteoporotic sites (hip, humerus, wrist, rib) was performed at baseline and after an average of 4.3 years. All incident fractures during the study period were confirmed by radiograph of the affected site. Results: 449 women (mean age 72.9±4.8 years) and 258 men (mean age 72.3±4.7 years) were included in the study. The age-adjusted incidence of non-vertebral fracture was 1710/100, 000 person-years in women and 630/100, 000 person-years in men (female/male ratio: 2.6). The age-adjusted incidence of hip fracture was 420/100.000 person-years in women and 90/100, 000 person-years in men (female/male ratio: 4.7). The incidence increases with age, particularly in women. Conclusions: The incidence of non-vertebral osteoporotic fracture in the elderly population was high, especially among women. Concerning hip fracture, these results emphasize that the incidence in the southern and southeastern regions of the country seems to be higher than the rates in the northern/northeastern population. Furthermore, our results reinforce the notion that the incidence of hip fracture in Brazilian older adults, particularly in women, is higher than in other Latin American populations, except Argentina. References: Kanis JA, Odén A, McCloskey EV, Johansson H, Wahl DA, Cooper C; IOF WorkingGroup on Epidemiology and Quality of Life. A systematic review of hip fractureincidence and probability of fracture worldwide. Osteoporos Int. 2012;23(9):2239-56. Schwartz AV, Kelsey JL, Maggi S, Tuttleman M, Ho SC, Jόnsson PV, Poόr G, Sisson de Castro JA, Xu L, Matkin CC, Nelson LM, Heyse SP. International variation in the incidence of hip fractures: cross-national project on osteoporosis for the World Health Organization Program for Research on Aging. Osteoporos Int. 1999;9(3):242-53. Castro da Rocha FA, Ribeiro AR. Low incidence of hip fractures in an equatorial area. Osteoporos Int. 2003;14(6):496-9. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5061